Performance evaluation of cellulose acetate (CA)/polyvinylpyrrolidone (PVP) membranes in the pervaporation separation of trimethyl borate/methanol azeotrope - Ozekmekci, Mehtap; Çopur, Mehmet (Turkish Energy, Nuclear and Mining Research Agency, 2025)
In this study, the performance of cellulose acetate (SA)/polyvinylpyrrolidone (PVP) blend membranes for the separation of trimethyl borate (TMB)/methanol azeotrope was investigated. The membranes were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), X-Ray diffractometer (XRD), thermogravimetric analysis (TGA) and contact angle measurements. The characteristic XRD peak intensity and contact angle of SA decreased with increasing PVP ratio. The effect of PVP ratio, feed temperature and methanol concentration in the feed were investigated in the pervaporation process. It was observed that flux increased and selectivity decreased with increasing PVP ratio. Feed temperature was found to have a positive effect on flux. The increase in the amount of methanol in the feed concentration caused the polymer chains to become more flexible, facilitating the diffusion of both methanol and TMB. Additionally, the reusability of the membrane was tested, and its physical and chemical structure integrity was confirmed by FTIR and SEM analyses. The optimum operating conditions for the SA-PVP-3 membrane were found to be 35°C temperature and azeotrope containing 25 wt% methanol. Under these operating conditions, the flux and selectivity were determined as 302.08 g/(m2h) and 46.92, respectively. © 2025, Turkish Energy, Nuclear and Mining Research Agency. All rights reserved.
Trimetil borat/metanol azeotropunun pervaporasyonla ayrılmasında selüloz asetat (SA)/ polivinilpirolidon (PVP) membranların performans değerlendirmesi
Keywords: Azeotrope; Methanol; Pervaporation; Trimethyl borate